Evaluation of the accuracy of reported noon positions from Soviet whaling factory ships - Ivashchenko, Yulia; Clapham, Phillip (J. Cetacean Res. Manage., 2023)
It has generally been assumed that the noon positions reported to the International Whaling Commission (IWC) by Soviet factory ships were accurate, despite that nation’s extensive falsification of catch records. In this paper, Soviet whaling industry reports are used to investigate this issue. Comparison of available track data from the reports with information submitted to the IWC through the BIWS shows that the officially reported data provide a reasonably accurate idea of general whaling effort, with minor discrepancies attributable to differences in precision or to geo-referencing. However, the Soviet report tracks sometimes include unreported excursions for the purpose of illegal whaling, and these were omitted from the data sent to the IWC.